Establishing and maintaining boundaries in teacher‐student relationships. Issue 137 (15th April 2013) - Bernstein‐Yamashiro, Beth; Noam, Gil G.
Abstract: Because schools rarely provide guidelines for teachers that outline how they should conduct personal relationships with students, teachers must wrestle individually with how to establish, communicate, and maintain clear boundaries in their interactions. As schools work to become more personal environments, school administrators will need to help teachers understand their roles as close advisors and mentors to students, while drawing and maintaining clear and obvious boundaries within these relationships. Students have clear ideas on how they prefer their teachers to interact with them and what feels comfortable in these relationships. Teachers also discuss from experience how they have managed to find comfortable ways to delimit relationships and continue to be effective mentors for students.